Sikap dan Niat Penggunaan Kod QR dalam Kalangan Pelajar UTHM - Nabilah Mohd Lazim; Nurazwa Ahmad; Noor Aslinda Abu Seman; Nor Kamariah Kamaruddin (Research in Management of Technology and Business, 2022)
Technology in Malaysia is now progressing to improve and increase the benefit of various parties for a better future. Among the examples of technology that has been created and used is the QR code that is used through smartphones. QR codes contain a large amount of data and the main advantage of QR codes compared to regular barcodes is that they contain information storage from both vertical and horizontal directions and that they are very easy to use. In higher education institutions in Malaysia, the integration of QR codes into aspects of learning and teaching is not yet widespread. The use of QR codes in universities nowadays is quite limited such as to record student attendance and access information on social activities organized in the university. Therefore, this study aims to identify the level and relationship between attitudes and intention to use QR codes among Bachelor’s degree students, Universiti Tun Hussein Onn Malaysia (UTHM) based on the Technology Acceptance Model (TAM) which involves elements of perceived usefulness, perceived ease of use, attitude toward using and behavioral intention to use. A total of 204 respondents were received through questionnaire responses. The results show that the evaluation of the level of attitude toward using and behavioral intention is high and there is a significant positive relationship (r = 0.891). The use of QR codes must be increased and more frequent among students and the quality of the use of QR codes must also be of a higher quality and in line with the increasing sophistication of technology today. Next, the University should diversify the use of QR codes in the campus environment because of the high acceptance of use among students which can benefit many parties in various affairs and activities.